The Effect of Fiscal Dependency on Sectoral Inequality in West Nusa Tenggara Province - Apriatun Damayanti; Abdul Manan; Irwan Suriadi (Universitas Batanghari Jambi, 2026)
This research seeks to examine the influence of fiscal dependence on sectoral disparities across regencies/cities in West Nusa Tenggara Province (NTB) during 2020–2024. Fiscal dependence is assessed using four primary indicators: Local Own-Source Revenue (PAD), General Allocation Fund (DAU), Special Allocation Fund (DAK), and Revenue Sharing Fund (DBH). In addition, sectoral disparity is determined via the Theil Index, derived from the allocation of Gross Regional Domestic Product (GRDP) across 17 economic sectors. The approach adopted is quantitative with a model panel data regression employing the Fixed Effect Model. Findings indicate that on an individual basis, PAD and DAU exerts a negative and significant impact on sectoral disparity. Contributing to disparity reduction via greater allocation flexibility. On the flip side, DAK and DBH individually show a positive and notable impact, suggesting that these forms of transfer funding are likely to heighten disparities across sectors due to their focus on specific areas. At the same time, every indicator of fiscal reliance demonstrates a positive and notable influence on sectoral disparities within NTB. These findings emphasize the importance of increasing regional fiscal independence and restructuring central transfer policies to promote equitable sectoral development in NTB.